Effects of Cardiomyocyte-Specific Deletion of STAT3–A Murine Model of Heart Failure With Preserved Ejection Fraction - Zhao, Weilin; Chen, Yanjia; Yang, Wenbo; Han, Yanxin; Wang, Zhiyan; Huang, Fanyi; Qiu, Zeping; Yang, Ke; Jin, Wei (Frontiers in Cardiovascular Medicine, 2020)
Abstract Aims The prevalence of heart failure with preserved ejection fraction (HFpEF) is increasing, but therapeutic options are limited. A new animal model of HFpEF is urgently needed for in-depth research on HFpEF. Signal transducer and activator of transcription 3 (STAT3) may affect the passive stiffness of myocardium, which determines cardiac diastolic function. We hypothesized that cardiomyocyte-specific deletion of STAT3 increases cardiac passive stiffness, which leads to the onset of a murine HFpEF-like phenotype. Methods and Results Cardiomyocyte-specific deletion of STAT3 (STAT3cKO) mice was generated by the Cre/FLOXp method. Compared with wild-type (WT) littermates, STAT3cKO mice showed increased cardiac fibrosis and cardiac hypertrophy. Furthermore, STAT3cKO mice showed increased serum brain natriuretic peptide (BNP) level, and growth stimulation expressed gene 2 (ST2) level. Other indicators reflecting cardiac passive stiffness and diastolic function, including end diastolic pressure volume relation, MV A value, MV E value, E/A and E/E’ had different fold changes. All these changes were accompanied by decreasing levels of protein kinase G (PKG). Bioinformatics analysis of STAT3cKO mice hearts suggested cGMP-PKG signaling pathway might be involved in the pathogenesis of HFpEF via regulating different biological functions. Conclusions Cardiomyocyte-specific deletion of STAT3 results in a murine phenotype reminiscent of the clinical manifestation of HFpEF partly by affecting myocardial PKG levels. Better understanding of the factors influencing HFpEF may potentially lead to novel therapeutic options.